Ruthenium-Catalyzed [2+2+2] Cycloaddition of α,ω-Diynes and Selenocyanates: An Entry to Selenopyridine Derivatives - Tran, Christine; Haddad, Mansour; Ratovelomanana-Vidal, Virginie (Synthesis, 2019)
A novel synthetic method for the preparation of selenopyridine derivatives, involving a [2+2+2] cycloaddition of α,ω-diynes and selenocyanates that is catalyzed by a ruthenium complex is described. This mild and straightforward reaction allows access to a wide range of selenopyridines with high yields and excellent regioselectivities, using dichloromethane or dichloroethane as solvents, at either 50 or 80 °C. Post-functionalization of halogenated cycloadducts via cyanation using copper and SNAr reaction provides substituted selenopyridines with good yields.
Keywords: ruthenium; cycloaddition; selenium; heterocycles; pyridines